Vocal range in the speech of users of low-dose oral contraceptives - Meurer, Elisea Maria; Capp, Edison (Journal of voice, 2017)
Summary Objective The study aimed to investigate the vocal range of oral contraceptive (OC) users aged between 20 and 30 years. Study Design This is a cross-sectional study. Methods Forty-eight women aged 20-30 years who used low-dose OCs and 24 age-matched women who did not use oral monophasic contraceptives (w/oOC) were enrolled. Acoustic analysis was performed using the Motor Speech Profile program, Model 4341 (Kay Elemetrics Corp). Data were analyzed using generalized estimating equation. Results In the w/oOC group, the highest vocal tones in the sentence uttered using exclamatory intonation were similar in the follicular phases of two cycles (F1: 289 ± 46 Hz; F2: 284 ± 61 Hz). In the luteal phase of the first cycle, the vocal tones were lower, whereas in the second cycle they were higher than the tones in both follicular phases (L1: 274 ± 42 Hz; L2: 291 ± 62 Hz) (P = 0.056). In the highest vocal tones of the same sentence uttered using exclamatory intonation, the OC group showed lower tones (284 ± 53 Hz) than the w/oOC group (298 ± 44 Hz) (P = 0.048). In the lowest vocal tones of utterances of joy, the OC group showed higher values (180 ± 39 Hz) than the w/oOC group (169 ± 44 Hz) (P = 0.024). The close proximity of the highest to the lowest values of utterances of joy in the OC group (321 ± 59 Hz and 180 ± 39 Hz), when related to the w/oOC group (338 ± 65 Hz and 169 ± 44 Hz), suggests a reduced vocal modulation. Conclusions The present findings demonstrate that the use of low-dose OCs influences the vocal range of women during menacme.
Online 3 November 2016
Gesehen am 29.10.2018